2012
DOI: 10.2337/db11-1624
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress–Induced JNK1/2 Activation Triggers Proapoptotic Signaling and Apoptosis That Leads to Diabetic Embryopathy

Abstract: Oxidative stress and apoptosis are implicated in the pathogenesis of diabetic embryopathy. The proapoptotic c-Jun NH2-terminal kinases (JNK)1/2 activation is associated with diabetic embryopathy. We sought to determine whether 1) hyperglycemia-induced oxidative stress is responsible for the activation of JNK1/2 signaling, 2) JNK1 contributes to the teratogenicity of hyperglycemia, and 3) both JNK1 and JNK2 activation cause activation of downstream transcription factors, caspase activation, and apoptosis, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 49 publications
(59 reference statements)
9
111
0
Order By: Relevance
“…Previously, we have identified caspase 8 and caspase 3 as initiator and effector caspases, respectively, in maternal diabetes-induced apoptosis (23,24). In this study, we demonstrated that trehalose treatment abolished maternal diabetes-induced caspase 3 and 8 cleavage (Fig.…”
Section: Maternal Diabetes Suppresses Autophagy In Neuroepithelial Cesupporting
confidence: 64%
See 3 more Smart Citations
“…Previously, we have identified caspase 8 and caspase 3 as initiator and effector caspases, respectively, in maternal diabetes-induced apoptosis (23,24). In this study, we demonstrated that trehalose treatment abolished maternal diabetes-induced caspase 3 and 8 cleavage (Fig.…”
Section: Maternal Diabetes Suppresses Autophagy In Neuroepithelial Cesupporting
confidence: 64%
“…Our mouse model of diabetic embryopathy was described previously (23,24). Briefly, female mice were intravenously (iv) injected daily with 75 mg/kg streptozotocin (STZ) over 2 days to induce diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting was performed as described previously (17,57). Briefly, E12.5 embryonic hearts were sonicated in ice-cold RIPA lysis buffer (Millipore, Bedford, MA).…”
Section: Mice and Reagentsmentioning
confidence: 99%